Comparison of Laryngeal Mask Airway (Classic) and I-Gel; Ease of insertion - Shahid Iqbal, M. Baqirali Khan, M. Zahid Hanif, Tahir Nazeer, M. Muazam Butt, Rifah, Amna Tahir, M.Arif Rasheed, Abdul Majid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: At the time of induction during general anaesthesia the different complication can occur with endotracheal tube. Supraglottic devices are alternative of endotracheal tube and it prevents such complications. Aim: To compare the frequency of ease of insertion with lma and i-gel® during general anaesthesia. Method: 270 patients of asa class p1 & p2 undergoing general anaesthesia for elective surgeries were included after taking informed consent. Patients were divided into two groups a (lma classic) & b (i-gel) by using random number table. Each group comprised of 135 patients. In both groups dose of propofol was 2.5mg /kg body weight was given intravenously within 30 sec along with nalbuphine 0.1 mg /kg body weight and midazolam 0.05mg / kg body weight. The study design was quasi experimental and sampling technique was purposive non probability convenience sampling. Chi square test was used and collected data was analysed with spss version 20. Result: The ease of insertion in the lma classic group was 82% while the ease of insertion in i-gel® was 84 %. Statistically there was no significant difference of ease of insertion between two groups (p value = 0.41). Conclusion: Both devices have same level of ease of insertion. Keywords: Lma (laryngeal mask airway classic), i-gel®, general anaesthesia, ease of insertion .